Concept design of hub reduction gear for off-road modified Toyota Hilux - Gullstrand, Joakim; Indridason, Sigurdur Svavar (Chalmers tekniska högskola / Institutionen för mekanik och maritima vetenskaper, 2017)
The task is to develop a proposal for a hub reduction gear for a Toyota Hilux for the company Arctic Trucks. The hub reduction should relieve stress on the powertrain, increase traction force and reduce speed from the increase in tire size. The gears has been developed, with analysis to give the expected life and low weight. Requirements on size and packaging has been considered. A full CAD model has been created with all necessary parts included to make a first prototype for testing. A 3D-printed version in scale 1:1 has been created for easy understanding of the final proposal. A spur gear compound planetary design has been chosen because of its simplicity and no axial load. The gear combination that fulfilled all set geometrical and stress constraints and was assessed to be the best option has the gear ratio of 2.19:1. The gear casing has been designed to act also as the upright with same mounting points as original upright and the original wheal bearing and break caliper can still be used. The added weight due to the hub reduction gear is 20.197 kg at each front wheel and is assumed to be slightly less than that in the rear due to smaller casing. The hub reduction has moved the hub 146mm outwards and therefore changed the ET offset of the rims from -115 to +31. A different ABS sensor is needed since the original one will not fit. The next step would be to do a prototype and tests the design. The gear manufacturing cost for 1 car is 56620 SEK and for 10 cars it is 255300 SEK.